(untitled) (Iranian Journal of Kidney Diseases, 2017)
Introduction. Both anemia and high doses of erythropoietin have been associated with increased mortality among dialysis patients. This study was conducted to evaluate the effective dose of erythropoiesis-stimulating agents. Materials and Methods. This multicenter nationwide cross-sectional study assessed adult patients on hemodialysis for at least 3 months from 80 hemodialysis centers in Iran. Demographic data, erythropoietin dose, and laboratory data were collected. Results. A total of 7009 prevalent hemodialysis patients were enrolled. Fifty-five percent of the patients had their hemoglobin levels within the target values. In those with a hemoglobin level of 8 g/dL to 10 g/dL, an erythropoietin dose of 10000 IU/wk to 12000 IU/wk led to a significant increase in hemoglobin level. A mean erythropoietin dose of 7700 IU/wk was effective in maintaining the target hemoglobin of 10 g/dL to 12 g/dL during a 3-month follow-up period. Improvement in hemoglobin level was associated with male sex, diabetes mellitus, and hemodialysis adequacy, and its deterioration with lower parathyroid hormone, calcium-phosphorus product, and creatinine levels; malnutrition; transfusion; and angiotensin-converting enzyme inhibitors and angiotensin receptor blockers (R2 = 29.1%, P < .001). A dosage of 66.5 IU/kg/wk led to 1 g/dL increase in hemoglobin in anemic patients. Conclusions. Data suggested that an estimated erythropoietin dose of 66.5 IU/kg/wk for each 1 g/dL hemoglobin level below the target could be used as a guide for prescription. A dosage of about 8000 IU/wk could help maintaining hemoglobin within the target. A longitudinal study is needed to estimate the required erythropoietin dose.